Should Canadian Medical Schools Implement a Widespread 3 Year Medical Curriculum? - Page, Douglas; Baranchuk, Adrian (Canadian Medical Education Journal, 2010)
Background: This paper addresses the potential costs and benefits of implementing a widespread 3 year medical curriculum across the country. Methods: We compared differences in curriculum, costs, workforce production, competency, exposure to experiences, timing of career choices, and maturity of students and physicians between 3 and 4 year programs. We accessed this information from 5 school’s online course outlines and by performing a broad search of the literature. Results- Three and four year medical programs have very similar curricular content. The most significant cost savings in a 3 year medical program are due to these students entering the workforce a year earlier. A 3 year program would add more physicians to our workforce initially; however, more doctors are produced over the long term by expanding class sizes. Test scores of graduates from 3 year programs in Canada and the US are similar to graduates from 4 year medical programs. A shorter program could limit the exposure of students to extra curriculars and force them to make earlier career decisions; however, time spent in electives appears to be similar. Conclusions: We do not find enough compelling evidence to advocate switching all medical schools in Canada to a 3 year medical program.